THE CONCEPT OF INSTILLING RELIGIOUS MODERATION VALUES IN CHILDREN IN THE FAMILY - syamsul bahri (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2022)
Religious moderation is a key spectrum that children want to strengthen in order to produce a family output that has tolerant attitudes and conduct, recognizes the presence of other parties, respects viewpoints, and does not push their will via violence. The goal of this research is to define the religious moderation ideals that must be established in youngsters in order to combat extremism. The descriptive qualitative approach was utilized, which involved examining national situations and conditions. In order to combat radicalism, the study's findings reveal that a strong national commitment, diversity, tolerance, peace, and the preservation of local culture are qualities that need to be taught and established in children in the home. Religious moderation is predicted to bring fresh new experiences in religious life today and in the future if it is instilled in children at a young age. Following up on these discoveries, enormous socialization of youngsters, particularly the millennial generation, is required in order to establish conceptual, scientific, and historical awareness, so that they are not occupied by nutrients that might ruin their knowledge.